THE INFLUENCE OF INNOVATION AND TECHNOLOGICAL FACTORS AT DEVELOPMENT OF PROPERTY SPHERE OF ECONOMY - V. Makedonskiy (Publishing House of the State University of Management, 2017)
This article is devoted to disclosure of such an economical category as innovation and technological factor. Considering studying the level of its influence on development to construction sector of economy, and suggesting stimulus measures of innovation activities.